The Implementation of INA-CBGs System Impact on Financial Performance of Public Hospital, the Indonesia Case: A Systematic Review - Happy, A (KnE Life Sciences, 2018)
Indonesia started the national health insurance system on 1 January 2014. In this system, there is only one insurer institution, BPJS Kesehatan, a social security agency established by the government to provide health insurance for Indonesian people. This new national health insurance system pays all claims based on package system called Indonesia Case-Based Groups (INA-CBGs). The aim of this review is to describe the application of the INA-CBGs system and its effect on financial performance of the public hospital and helping them in identifying and anticipating problems in implementation of the INA-CBGs system. This review shows prism flowchart using Proquest and Portal Garuda with INA-CBGs, public hospital finance performance, universal health coverage, and Indonesia as the keywords. From the 15 selection research journals, we found that the implementation of the INA-CBGs system with the prospective payment system can provide a positive impact on the financial performance in public hospital, when the hospital could reduce inefficient cost of treatment. Furthermore, public hospitals achieve a surplus since they receive a donation from the government for salary expenses and investment-related expenses. Public hospital management in Indonesia should consider the competence of their accounting and financial managers so they can manage their hospitals properly. Each public hospital management must have a strategy and innovation to improve the quality of service so they can compete with other hospitals and financial performance can be improved in this JKN era. Keywords: INA CBGs, Public Hospital financial performance, universal health coverage, Indonesia